The Development of Prism and Pyramid Teaching Material Assisted by Construct 2 Software - Euis Suwangsih; Nelly Fitriani; Utari Sumarmo (IKIP Siliwangi, 2023)
The aim of the research is to develop teaching materials assisted by media construct 2 software that are practical and appropriate for use in the learning process. The research method used is Research and Development (R&D) using the ADDIE model. The research was conducted at SMPN 3 RancabaliÂ with 12 class VIII students at Rancabali 3 Middle School for limited trials and 9 students at SMPN 2 Rancabali and 9 students at SMPN 1 Rancabali Public for a wider trial and 27 VIII C class students as an experimental class and 27 class VIII A students as the control class for product trials. The validators consist of ICT experts, subject matter experts and teachers. The data collection technique was in the form of a response questionnaire from students and teachers. The research results of the products developed were in accordance with the ADDIE research method with product feasibility categories based on ICT expert validation of 81.25%, material experts 85% and teachers 88% are all included in the very decent category. Products that have been validated are then tested on students through limited trials, wider trials and product trials and students are given practicality questionnaires with a final average result of 83.56% included in the very practical category. Based on the validation results of ICT experts, material experts and student and teacher responses, it was concluded that the teaching materials assisted by the media construct 2 software are valid and appropriate for use in learning. For further research, the researcher hopes to be able to develop teaching materials better according to the suggestions from the respondents.